"You can try to press different emotional buttons": The conflicts and strategies of eliciting emotions for fundraisers. Issue 4 (17th November 2017) - Dean, Jon; Wood, Rachel
Abstract : In a competitive climate in which charities must increasingly rely on fundraising with the public, emotions such as hope, guilt, and fear are powerful tools that can be used strategically to secure donations or participation. This paper explores data from interviews with 23 fundraisers and voluntary sector workers, managers, and officials, to argue that decisions around how, why, and when to invest in the elicitation of emotion in fundraising are often difficult and conflicted, with some identifying a battle between ethics and effectiveness. We identify 3 key levels of conflict that must be negotiated: at the level of the charity sector, where the emotional ethics particularly of larger charities have been met with some resistance from the public and press; at the level of the organisation itself, where the ethics of representation are often a subject of conflict between fundraising and other departments such as policy; and, finally, at the experiential level of individual fundraisers themselves, who report being routinely internally conflicted around the rights and wrongs of using emotion in their work. A strategic approach to eliciting emotion emerges in the data as a useful way to address some of these areas of conflict, with fundraisers making careful "balancing" decisions about how and with whom to mobilise certain emotions at specific times.